Effect of weed control on yield and quality of malt barley (Hordeum vulgare) - Singh, Khushkaran Singh; Singh, Kanwaljit; Singh, Gurbax; Kumar, Dinesh (Journal of Cereal Research, 2016)
The experiment was conducted at the Research Farm of the KhalsaCollege, Amritsar during Rabi seasons of 2013-14 and 2014-15 to studythe weed control efficacy of different herbicides in barley. Minimumweed dry weight was recorded in clodinafop (60g) + metsulfuron(4g/ha), which was significantly lower than isoproturon (936 g) +metsulfuron (4 g/ha), isoproturon (936 g) + 2, 4-D (500 g/ha), pinoxaden(50 g/ha), fenoxaprop-p-ethyl (100 g/ha), isoproturon (936 g/ha), handweeding and weedy check during both the years. Maximum plantheight, , dry matter accumulation, effective tillers, ear length, numbersof grains per ear, test weight, grain yield and malt yield were recordedin clodinafop (60 g) + metsulfuron (4 g/ha ) which was significantlyhigher than isoproturon (936 g) + metsulfuron (4 g/ha), isoproturon(936 g) + 2, 4-D (500 g/ha), pinoxaden (50 g /ha), fenoxaprop-p-ethyl(100 g/ha), isoproturon (936 g/ha), hand weeding and weedy checkin both the years.